Analisis Penerapan Pernyataan Standar Akuntansi Pemerintah PSAP 07 pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten PALI - Muhammad Rajesh Putra Sandof; Yuliana Sari; Desi Indriasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The major objective of this research is to determine whether PSAP 07 is suitable for the identified, measured, evaluated, released and disposed of, disclosed, and depreciated fixed assets of the PALI Regency Financial and Fixed Asset Management Agency. The Agency was the site of the research. The focus here is on descriptive qualitative research. The research for this project made use of both official and unofficial sources of data. The data was gathered via interviews with people who were actively involved in managing regional assets and money. The impact of PSAP No. 07 on the fixed assets of BPKAD Pali Regency was investigated in this research using qualitative descriptive analysis. The results show that PSAP No. 7 has been satisfactorily handled by BPKAD Pali Regency with respect to the FMA of PALI Regency in terms of recognition, measurement, assessment, disclosure, disposal, and depreciation.